The Effects of Political Reservations on Credit Access and Borrowing Composition: New Evidence from India - Chon-Kit Ao; Somdeep Chatterjee (Global Labor Organization (GLO), 2018)
We estimate the impacts of mandated political reservation for minorities on household credit access and borrowing behavior. To identify causal effects, we exploit the exogenous state-time variation in the allocation of constituencies (electoral districts) to the two reserved minority groups in Indian states. Using a household level panel data with observations before and after the redistricting, we find that the effect is concentrated on the disadvantaged population groups. Political reservation for Scheduled Tribes (STs) increases household probability of getting a loan by 3.7 percentage points, while political reservation for Scheduled Castes (SCs) has no effect on the likelihood of getting a loan. However, conditional on having a loan, reservation for SCs does lead to fewer but larger loans. We also find considerable changes in household borrowing composition.
Keywords: D78; J15; J78; O12; 330; Affirmative action; Political reservation; Credit access; Borrowing composition